Membranes and membrane technologies II - Kolisnychenko, Stanislav (Specialized collections ;, 2020)
The topic collection "Membranes and Membrane Technologies II" of the latest scientific researches published by Trans Tech Publications from 2018 up to 2019 covers a wide range of engineering solutions in the field of properties research, development and production of various types of membranes, and their use in the technologies for the treatment of the drink water and wastewater, gas separation, etc. We hope this collection will be useful and interesting to a broad audience of researchers and engineers. Polymeric Membrane, Inorganic Membrane, Composite and Hybrid Membranes, Liquid Membrane, Separation, Filtration, Reverse Osmosis, Water and Wastewater Treatment, Desalination, Pervaporation, Distillation, Membrane Technology, Gas Separation Materials Science, Mechanical Engineering, Manufacturing.